THE STRUCTURE AND FACTORS OF THE CYCLIC RECURRENCE OF REGIONAL LABOR MARKET - Yakimova, L. P. (The actual problems of regional economy development, 2017)
The article focused on the development of methodological principles of research of the regional labor market in the aspect of its nonlinear dynamics and identification of complex endogenous and exogenous factors of cyclical. We applied filter Hodrika – Prescott for the separation of long-term trends and cycles in dynamic indicators and cyclical factors of labor market Chernivtsi region. In this paper we have substantiated multi-cyclical of regional labor market, we estimated volatility and persistence of cycles indicators and their relation to the business cycle and also identified leading, lagging and coincident cyclical indicators of unemployment rate. We constructed an econometric model with dummy variables for forecasting of seasonal fluctuations unemployment rate. The developed software can be used in the preparation of national and regional programs of socio-economic development and promote employment.